Intraburst kinetic properties of the GABAA receptor main conductance state of mouse spinal cord neurones in culture. - Twyman, R E (1990)
1. The intraburst kinetic properties of the main conductance state of gamma-aminobutyric acidA (GABAA) receptor channels in excised outside-out patches obtained from somata of mouse spinal cord neurones in cell culture were investigated using the patch clamp single-channel recording technique. 2. At 2 microM-GABA, the burst duration distribution was fitted by four exponential functions with time constants of 0.5, 2.4, 8.3 and 31.8 ms. 3. At 0.5, 1 and 2 microM-GABA, frequency distribution histograms of the number of apparent openings per burst were best fitted by three geometric functions with similar mean numbers (1.1, 1.9 and 3.6) of openings per burst. The proportion of bursts with a mean of 1.1 openings per burst decreased with increased GABA concentration while the proportion of bursts with means of 1.9 and 3.6 openings per burst increased with GABA concentration. 4. Analyses of GABA receptor channel intraburst kinetics were performed at all three GABA concentrations. The results were similar for all concentrations, but detailed results are presented only for 2 microM-GABA. 5. The open time distribution for all intraburst openings was best fitted by three exponential functions with time constants of 0.6, 2.9 and 8.9 ms. 6. Intraburst open time and total open time distributions for bursts with one to five openings were fitted with two or three exponential functions or gamma distributions, respectively. The number of components, time constants and relative areas were similar for both distributions. 7. The distributions of open times for the nth opening within bursts of k openings were similar for bursts containing two to five openings. The distributions of open times for the nth opening of all bursts varied with position within the burst. The distributions shifted to longer openings as the opening number increased from one to five. 8. The distributions of all closings within all bursts or within bursts with two to five openings and of closings relative to position in all bursts could be fitted by two exponential functions with time constants of about 0.20 and 3.1 ms and relative proportions of 0.55 and 0.45 at all GABA concentrations. 9. The total closed time distributions for bursts containing two to four closings, however, were all best fitted with only a single gamma distribution with a time constant of 1.3 ms.(ABSTRACT TRUNCATED AT 400 WORDS)